Analisis Nilai Moral dan Nilai Sosial dalam Cerpen Lelaki Sejati karya Putu Wijaya - Destiani Sagita; Raden Ika Mustika; Mekar Ismayani (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
In the development of this era, literary works are easier to enter in the lives of literary connoisseurs, literary works that are often encountered in society, one of which is short stories or we often call short stories. A short story but has a very important meaning in life, has moral and social values related to today's era. As in the short story "The True Man" by Putu Wijaya, which has a high imagination, and the process of telling a coherent story content needs to be given an appropriate assessment by familiar characters, namely a mother and her daughter who are conducting a question and answer process about the life of a real man. in this day and age. This study aims to analyze the moral and social values in the short story of the True Man by Putu Wijaya. This research can be useful for readers and can improve the ability to analyze the moral and social values contained in the short story. The method in this study is a qualitative descriptive method. The data source is taken from one of Hardiyanti Nurill's blogs on the Internet. The data were analyzed using a sociology of literature approach, namely analyzing and interpreting moral and social values. The results of the analysis found the moral and social values of the short story for a real man, namely, the moral value contained in Putu Wijaya's short story for a real man is in the part when the mother explains what a real man looks like to her teenage daughter. The social value contained in the short story is in the section where a young woman asks her mother about what a real man is like.